Broadcasting in the Era of Digital Technologies: A Perceptual Assessment of Imo State Based Journalists - Kizito Nzube Alaekwe; Cajetan O. Iheanacho; Alexander Chima Onyebuchi; Loveth Okoye; Chinwe H. Nze; Emeka Williams Etumnu (Universitas Ahmad Dahlan, 2025)
This study examines how digital technologies influence broadcasting practices among journalists in Imo State, Nigeria. Using a census-based survey (N=200), findings show that digital technologies significantly enhance news gathering, production speed, and dissemination efficiency (Mean=3.5). However, inadequate ICT training and poor infrastructure remain constraints. The study concludes that digital convergence has reshaped broadcast workflows, requiring sustained capacity building and policy support. The key contribution of this study was that it gave insights on how journalists perceive Digital Technologies in modern day broadcasting as well as how it is has influence the practice of broadcasting in the era of digital technologies especially in Imo State.